ANALYZING THE IMPACT OF THE BUSINESS LICENSING EASE POLICY FOR DRUG AND FOOD MSME BUSINESS ACTORS: A CASE STUDY IN EAST KALIMANTAN PROVINCE FROM 2018 TO 2023 - Wulandari, Ratih; Kenyowulan, Pranandari; Juwitaningsih, Marheni; Jaffar, Akhmad Kamaluddin (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2023)
The limited number of products registered with the Indonesian FDA by MSMEs is primarily attributable to their ignorance of the procedures involved in obtaining product authorization. The Samarinda provincial office of the Indonesian Food and Drug Administration has launched the "Si Jebol" program, which assists MSMSEs in obtaining product authorization. This study aims to determine how the policy of ease of business licensure for pharmaceutical and food micro, small, and medium enterprises (MSMEs) affected product authorization in the province of East Kalimantan from 2018 to the first semester of 2023. This research methodology employs a descriptive qualitative analysis of secondary data obtained from the Samarinda annual reports of the provincial office of the Indonesian FDA. The findings indicate that the convenience of business licensing policy, which was executed by the Provincial office of the Indonesian FDA in Samarinda, effectively stimulates the issuance of product authorization permits. The obstacles encountered by MSMEs during the registration process for product authorization may serve as the foundation for future policies designed to assist MSMEs. Additional research on the challenges encountered by micro, small, and medium enterprises (MSMEs) is crucial in order to establish intervention strategies that the provincial office of the Indonesian FDA in Samarinda can implement. Keywords: Indonesian FDA, Product Authorization, East Borneo, Policy, Micro Small and Medium Enterprise (MSME)